Penerapan Metode Tilawati Dalam Pembelajaran Al-Qur’an Di Pondok Pesantren Hidayatul Mubtadi’ien Kota Bengkulu - Rosyid, Muhammad Agus Ainur; Alimni, Alimni (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2024)
This study aims to analyse the planning, implementation, and evaluation of the application of the Tilawati method at Hidayatul Mubtadi'ien Islamic Boarding School, as well as identify the supporting and inhibiting factors. The research method employed is a descriptive qualitative approach, utilizing data collection techniques that include in-depth interviews, observation, and documentation studies. The results showed that the planning of the application of the Tilawati method involved selecting teaching staff with syahādah, preparing learning objectives based on the stages of the students' abilities, and providing media and teaching materials, such as the Kitab Tilawati Volumes 1-6. The implementation of this method combines classical and individual approaches, which have proven effective in improving the ability to read the Qur'an. The main obstacles identified include santri discipline and difficulty in reciting Rost, while supporting factors include the quality of teaching staff, infrastructure, and institutional support. Strategic solutions, such as intensive training, rescheduling sleeping habits, and utilizing the Tilawati Mobile application, successfully overcame the obstacles. This study has implications for the development of technology-based Qur'an learning methods and holistic approaches to improve the quality of education in pesantren.